2005
DOI: 10.1007/s00441-005-0077-0
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 2 facilitates the differentiation of transplanted bone marrow cells into hepatocytes

Abstract: We have developed an in vivo mouse model, the green fluorescent protein (GFP)/carbon tetrachloride (CCl(4)) model, and have previously reported that transplanted GFP-positive bone marrow cells (BMCs) differentiate into hepatocytes via hepatoblast intermediates. Here, we have investigated the growth factors that are closely related to the differentiation of transplanted BMCs into hepatocytes, and the way that a specific growth factor affects the differentiation process in the GFP/CCl(4) model. We performed immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 37 publications
1
25
0
1
Order By: Relevance
“…Our previous study and those of others have demonstrated that sodium butyrate, an inhibitor of histone deacetylase, induces the differentiation of ES cells into hepatocytes [12][13][14][15] . Some researchers have also shown that at the time of liver specification, BMP4 expression in the mesoderm surrounding the foregut endoderm is required for the induction of hepatic fate [18][19][20] and that bFGF from the cardiac mesoderm is required for the initiation of liver bud development in the anterior definitive endoderm [21,22] . Zhou [23] have reported a synergistic effect between bFGF and BMP4 in inducing hepatocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study and those of others have demonstrated that sodium butyrate, an inhibitor of histone deacetylase, induces the differentiation of ES cells into hepatocytes [12][13][14][15] . Some researchers have also shown that at the time of liver specification, BMP4 expression in the mesoderm surrounding the foregut endoderm is required for the induction of hepatic fate [18][19][20] and that bFGF from the cardiac mesoderm is required for the initiation of liver bud development in the anterior definitive endoderm [21,22] . Zhou [23] have reported a synergistic effect between bFGF and BMP4 in inducing hepatocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that at the time of liver specification, the induction of hepatic fate requires BMP4 expression in the mesoderm surrounding the foregut endoderm [18][19][20] . Derived from the cardiac mesoderm, bFGF is required for the initiation of liver bud development in the anterior definitive endoderm [21,22] . Additional studies have indicated a synergistic effect between BMPs and FGFs in inducing hepatocyte differentiation [23] .…”
Section: Introductionmentioning
confidence: 99%
“…Um dos principais fatores de crescimento utilizados em cultura é o fator de crescimento do fibroblasto (FGF), um importante mitógeno que já se demonstrou importante no desenvolvimento hepático (ISHIKAWA et al, 2006). Neste sentido, foi demonstrado através de ensaio imunoenzimático que o transplante de AD-MSCs pré--tratadas com fator de crescimento fibroblástico básico (bFGF) em ratos com lesão hepática, induzida por CCl 4 durante oito semanas, atenua a fibrose hepática através do aumento da expressão de metaloproteinases (KAMADA et al, 2009).…”
Section: Atividade Fibrinolíticaunclassified
“…Based on these promising characteristics, MSC have now been tested in a wide variety of injury/disease model systems for their ability to generate hepatocytes and correct these liver defects. Using MSC isolated from a variety of mouse, rat, and human tissues, investigators have now provided evidence that MSC can mediate varying degrees of correction/repair of the liver following injury due to partial hepatectomy [126,[130][131][132][133], treatment with the toxin CCl4 [134][135][136][137][138][139][140][141][142][143][144][145], injury induced by allylalcohol [146,147], and treatment with 2-acetylaminofluorene [139].…”
Section: Mesenchymal Stem Cells Differentiate In Vivo Into Hepatocytesmentioning
confidence: 99%